Proceedings of the International Working Conference on Advanced Visual Interfaces 2016
DOI: 10.1145/2909132.2909265
|View full text |Cite
|
Sign up to set email alerts
|

Target Expansion Lens

Abstract: To enhance pointing tasks, target expansion techniques allocate larger activation areas to targets. We distinguish two basic elements of a target expansion technique: the expansion algorithm and the visual aid on the effective expanded targets. We present a systematic analysis of the relevance of the visual aid provided by (1) existing target expansion techniques and (2) Expansion Lens. The latter is a new continuous technique for acquiring targets. Expansion Lens namely, uses a round area centered on the curs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Lastly, we could also observed that the method of IFC was significantly slower than the other four methods (p < 0.0005), and in general IFC had significantly higher error rate than the other four methods except for the cases of A = 768 and DRATIO = 1.5. IFC had a better performance than other tested area cursor techniques in their paper, this might be owing to IFC was the only technique that used implicit display style in their experiment, while in our paper, all tested area cursor techniques used implicit display style and the effect of different display styles on performance, as reported in [15,28], could be minimized. Since AVC, AVC+M.…”
Section: Designmentioning
confidence: 52%
See 2 more Smart Citations
“…Lastly, we could also observed that the method of IFC was significantly slower than the other four methods (p < 0.0005), and in general IFC had significantly higher error rate than the other four methods except for the cases of A = 768 and DRATIO = 1.5. IFC had a better performance than other tested area cursor techniques in their paper, this might be owing to IFC was the only technique that used implicit display style in their experiment, while in our paper, all tested area cursor techniques used implicit display style and the effect of different display styles on performance, as reported in [15,28], could be minimized. Since AVC, AVC+M.…”
Section: Designmentioning
confidence: 52%
“…Different from the standard Voronoi partition used in the ordinary Bubble area cursor, we hypothesized that the dynamic partition of the additively weighted Voronoi diagram (AWVD) in AVC would improve the efficiency of the correction cursor movement. Note that other literature [15,24] considered that the whole target-selection task involves extra phases besides the ballistic and correction phases, such as the searching phase before the starting of mouse movement, and the verifying phase after the correction movement and before the mouse clicking occurs. However, in this work, we do not focus on these extra phases, as the time spending on them would not significantly affect by area cursor techniques.…”
Section: Additive Voronoi Cursormentioning
confidence: 99%
See 1 more Smart Citation